Die Korrespondenz Ferdinands I. Familienkorrespondenz Bd. 5: 1535 und 1536 - Hofinger, Bernadette (2015)
The main topics of the correspondence between Ferdinand I and his siblings Charles V and Mary of Hungary edited in this volume are Ferdinand's attempts to achieve peace with Johann Szapolyai in Hungary; the clashes with the Ottomans; the Tunis campaign of Charles V; the conflict with Francis I of France after the death of the last Sforza Duke of Milan; and the confessional division in the Holy Roman Empire.